Fast one-dimensional wave-front propagation for x-ray differential phase-contrast imaging - Wolf, Johannes; Malecki, Andreas; Sperl, Jonathan; Chabior, Michael; Schuettler, Markus; Beque, Dirk; Cozzini, Cristina; Pfeiffer, Franz (Biomedical Optics Express, 2014)
Numerical wave-optical simulations of X-ray differential phase-contrast imaging using grating interferometry require the oversampling of gratings and object structures in the range of few micrometers. Consequently, fields of view of few millimeters already use large amounts of a computer’s main memory to store the propagating wave front, limiting the scope of the investigations to only small-scale problems. In this study, we apply an approximation to the Fresnel-Kirchhoff diffraction theory to overcome these restrictions by dividing the two-dimensional wave front up into 1D lines, which are processed separately. The approach enables simulations with samples of clinically relevant dimensions by significantly reducing the memory footprint and the execution time and, thus, allows the qualitative comparison of different setup configurations. We analyze advantages as well as limitations and present the simulation of a virtual mammography phantom of several centimeters of size.
CRIS-Team Scopus Importer:2023-03-08